2015
DOI: 10.1111/1756-185x.12677
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of weekly leflunomide for the treatment of early rheumatoid arthritis: a randomized, multi‐center study

Abstract: Aim: The aim of this study was to determine the efficacy and safety of a weekly dose of leflunomide (50 mg/ week) in early rheumatoid arthritis patients with mild or moderate disease activity. Methods:The patients of early rheumatoid arthritis (ERA) with mild or moderate disease activity were randomly selected for inclusion in this study and were assigned to either the treatment group (leflunomide 50 mg/week, LEF50) or the control group (leflunomide 10 mg/day, LEF10). All patients were treated for 24 weeks. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
2
0
2
Order By: Relevance
“…One study compared a loading dose of leflunomide (100 mg×1 for 3 days) with a fixed dose of 20 mg daily and did not show differences in efficacy but a better safety profile for the fixed dose 16. A weekly dose of 50 mg leflunomide showed similar benefits to a daily dose of 10 mg leflunomide for the treatment of mild-to-moderate early RA 17. The latter however was an open superiority study with a high RoB and 10 mg leflunomide daily is considered a suboptimal dose.…”
Section: Resultsmentioning
confidence: 99%
“…One study compared a loading dose of leflunomide (100 mg×1 for 3 days) with a fixed dose of 20 mg daily and did not show differences in efficacy but a better safety profile for the fixed dose 16. A weekly dose of 50 mg leflunomide showed similar benefits to a daily dose of 10 mg leflunomide for the treatment of mild-to-moderate early RA 17. The latter however was an open superiority study with a high RoB and 10 mg leflunomide daily is considered a suboptimal dose.…”
Section: Resultsmentioning
confidence: 99%
“…Roz-waża się również zmniejszenie stosowanej docelowej dawki leku do 10 mg/dobę, zwłaszcza w przypadku politerapii [26]. W ostatnich latach dyskutuje się nawet nad zmniejszeniem dawki leflunomidu do 50-100 mg/tydzień [27,28], choć nie wszystkie badania potwierdzają równoważność tak małych dawek leflunomidu [29]. Wydaje się, że maksymalne prawdopodobieństwo sukcesu klinicznego oraz jednocześnie największego bezpieczeństwa terapii można uzyskać, wybierając dawkę, która utrzymuje docelowe stężenie leku w surowicy powyżej 13 mg/l.…”
Section: Znaczenie Dawki Leflunomiduunclassified
“…The results of this study showed that weekly administration is easy, low cost, and has good safety. This treatment protocol also increased patient compliance despite maintaining the therapeutic properties of leflunomide (6).…”
Section: Supporting Evidencementioning
confidence: 99%